THE EFFECT OF PERSONAL SAFETY TRAINING PROGRAM FOR PRE SCHOOL CHILDREN - (:unkn) unknown (My University, 2020)
Introduction:Preschool children are more vulnerable and at risk to social, physical and environmental risks that threaten their personal safety. It is important to teach children in this period how to protect their personal safety. Method:This study was aimed to determine the effectiveness of the body safety education program to preschool students. The study design was pre-post-test, non-randomized experimental and control group model. The sample size was calculated by G*power analysis. Accordingly, it was calculated that 34 students (total 78 students) should be sampled in each group with 80% power and 5% error margin. The study was completed with 80 students. Data were collected by personal information form and body safety information questionnaire. Written informed consent was obtained from the families before the study. The 5-session program, each of which lasted for 25 minutes, was implemented in 5 weeks for the training group (n=40). No intervention was applied to the control group. Chi-square test and Mc Nemar test were used for data analysis. Result:There was a significant difference between the pre-posttest responses of the children in the intervention group to the question in "Do you drink the drugs you find without telling the parent / teacher?” (p <0.05). There was a significant difference between the pre-posttest answers of the children in the intervention group to the questions “Would you enter the sea or pool alone without a grand (mother, father, relative)? or play with water?”(p <0.05). There was a significant difference between the pre-posttest answers of the training group, "When you're alone at home, if someone you don't know knocks on, will you open it?” and “if person who you don't know calls to play with you, you would go?” (p <0.05). There was no statistically significant difference between the pre-posttest answers of the control group to the all questions (p> 0.05). Conclusion:As a result, body safety education program was effective in informing students about poisoning, communication with strangers and drowning.